Prácticas discursivas sobre las drogas en una institución educativa rural en la ciudad de Cuenca - Guzmán Vásquez, Irma Catalina (2023)
The present research work has the purpose of knowing the discursive practices about drugs in a rural educational institution in the city of Cuenca, the same one that tries to understand the productions of meanings that teachers, students and legal representatives assign to drugs. For this purpose, this research is based on social constructionism that applies a qualitative methodology in which the technique of focus groups was considered as a reference, in order to obtain in-depth information, which will open paths to new research related to the issue. Finally, the results obtained from this work may contribute to society and the State.